Penerapan Sistem Remunerasi dan Kinerja Pelayanan - Soetisna, Tri Wisesa; Ayuningtyas, Dumilah; Misnaniarti, Misnaniarti (Kesmas, 2015)
Remuneration can influence worker`s motivation, and improve their performance. Likewise in hospital as capital-intensive, human resources-intensive as well as knowledge and technology-intensive health care institution. This study aimed to analyze employee’s perception of remuneration system implementation and adult cardiac surgery services unit’s performance at hospital. This study used a mixed method approach (quantitative and qualitative). Quantitative study design was cross-sectional using questionnaire for self-assesment. Meanwhile, qualitative study design was descriptive conducted through focus group discussion and document review on data in forms of schedule book, registration book, nursing notes and medical records. Data collection was conducted in 2013 at one hospital in Jakarta. Respondents/informants were functional medical staff, nurses, and administration staff amounted to 29 people. Data was analyzed using univariate and content analysis techniques. Results showed most functional medical staff dan nurse were unsatisfied (71.2%) with several things in remuneration system implementation, such as in payroll system and grading determination. However, adult cardiac surgery services unit’s performance is increasing every year before and after the implementation of remuneration system. This hospital is expected to improve the remuneration system in accordance with policy and arrange incentive formulation that is more appropriate with current condition as well as followed with proper socialization and periodical evaluation. Remunerasi dapat memengaruhi motivasi pegawai sekaligus meningkatkan kinerjanya. Demikian halnya di rumah sakit sebagai institusi pelayanan kesehatan yang padat modal, sumber daya manusia serta padat ilmu dan teknologi. Penelitian ini bertujuan untuk menganalisis persepsi pegawai terhadap implementasi sistem remunerasi dan kinerja unit pelayanan bedah jantung dewasa (UPBJD) di rumah sakit. Penelitian ini menggunakan pendekatan mixed methods (kuantitatif dan kualitatif). Desain penelitian kuantitatif adalah potong lintang menggunakan instrumen kuesioner self-assessment. Sedangkan desain penelitian kualitatif adalah deskriptif, dilakukan melalui focus group discussion dan telaah dokumen pada data berupa buku jadwal, buku registrasi, catatan keperawatan, dan rekam medis. Pengambilan data dilakukan pada tahun 2013 di salah satu rumah sakit di Jakarta. Responden/informan adalah staf medis fungsional, perawat, dan petugas administrasi berjumlah 29 orang. Data dianalisis secara univariat (metode kuantitatif), dan content analysis (metode kualitatif). Hasil penelitian menunjukkan bahwa sebagian besar staf medis fungsional dan perawat tidak puas (71,2%) dengan beberapa hal dalam penerapan sistem remunerasi, seperti pada sistem penggajian dan penentuan grading. Terlihat kinerja unit pelayanan bedah jantung dewasa mengalami kenaikan setiap tahun sebelum dan setelah penerapan sistem remunerasi. Diharapkan agar rumah sakit ini dapat memperbaiki sistem remunerasi yang sesuai ketentuan kebijakan dan menyusun formulasi insentif dan bonus yang lebih sesuai dengan kondisi saat ini serta perlu dilakukan sosialisasi yang tepat dan evaluasi secara berkala.